Given the equation:
Hg(l) + Cl₂(g) ⟶ HgCl₂(s) ΔH = -224 kJ
We can rearrange the given equation to find the enthalpy change for the process:
HgCl₂(s) ⟶ Hg(l) + Cl₂(g)
Since the enthalpy change for the reverse reaction is equal in magnitude but opposite in sign, we have:
ΔH = 224 kJ
Therefore, the enthalpy change for the process:
Hg₂Cl₂(s) ⟶ 2Hg(l) + Cl₂(g)
is 224 kJ.
Calculate ΔH for the process: Hg₂Cl₂(s) ⟶ 2Hg(l) + Cl₂(g) from the following information:
Hg(l) + Cl₂(g)⟶HgCl₂(s) ΔH = −224 kJ
skyisabel1953
1 answer